Altered calcium signaling in colonic smooth muscle of type 1 diabetic mice - Touw, Ketrija (American Physiological Society, 2012)
Seventy-six percent of diabetic patients develop gastrointestinal symptoms, such as constipation. However, the direct effects of diabetes on intestinal smooth muscle are poorly described. This study aimed to identify the role played by smooth muscle in mediating diabetes-induced colonic dysmotility. To induce type 1 diabetes, mice were injected intraperitoneally with low-dose streptozotocin once a day for 5 days. Animals developed hyperglycemia (>200 mg/dl) 1 wk after the last injection and were euthanized 7–8 wk after the last treatment. Computed tomography demonstrated decreased overall gastrointestinal motility in the diabetic mice. In vitro contractility of colonic smooth muscle rings from diabetic mice was also decreased. Fura-2 ratiometric Ca(2+) imaging showed attenuated Ca(2+) increases in response to KCl stimulation that were associated with decreased light chain phosphorylation in diabetic mice. The diabetic mice also exhibited elevated basal Ca(2+) levels, increased myosin phosphatase targeting subunit 1 expression, and significant changes in expression of Ca(2+) handling proteins, as determined by quantitative RT-PCR and Western blotting. Mice that were hyperglycemic for <1 wk also showed decreased colonic contractile responses that were associated with decreased Ca(2+) increases in response to KCl stimulation, although without an elevation in basal Ca(2+) levels or a significant change in the expression of Ca(2+) signaling molecules. These data demonstrate that type 1 diabetes is associated with decreased depolarization-induced Ca(2+) influx in colonic smooth muscle that leads to attenuated myosin light chain phosphorylation and impaired colonic contractility.